2019
DOI: 10.1016/j.ijrobp.2018.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects of Radiation Prime the Brain Microenvironment for Accelerated Tumor Growth

Abstract: Irradiation of normal brain primes the targeted cellular micro-environment for aggressive tumor growth when naïve (not previously irradiated) cancer cells are subsequently introduced. The resultant growth-pattern is similar to the highly aggressive pattern of tumor regrowth observed clinically following therapeutic radiotherapy. The mouse model offers an avenue for determining the cellular and molecular basis for the aggressiveness of recurrent GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 16 publications
4
29
0
Order By: Relevance
“…These findings augment growing literature that illustrate the impact of the irradiated tumor microenvironment on tumor behavior [18]. Duan et al [13] previously reported a radiation dose-dependent increased growth rate of mouse GBM cells within c57Bl6 mice upon delivery of (0, 20, 30, or 40 Gy by stereotactic radiation to the ipsilateral hemisphere.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These findings augment growing literature that illustrate the impact of the irradiated tumor microenvironment on tumor behavior [18]. Duan et al [13] previously reported a radiation dose-dependent increased growth rate of mouse GBM cells within c57Bl6 mice upon delivery of (0, 20, 30, or 40 Gy by stereotactic radiation to the ipsilateral hemisphere.…”
Section: Discussionsupporting
confidence: 79%
“…A growing body of literature has elucidated the substantial impacts of radiotherapy on non-tumor cells present in the tumor microenvironment and surrounding CNS parenchyma [10,11]. Although radiation remains standard of care and despite the nearly uniform GBM recurrence rates, we and others have made the concerning observation that the radiated microenvironment actually increases the aggressiveness of GBM cells implanted into an irradiated brain [12,13,14]. To date, studies reporting this phenomena have each evaluated a single cell line, leaving open the question of how widespread this susceptibility to increased aggressiveness may be across the clinical and moleulular spectrum of human GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has demonstrated that co- implantation of radiated with non-radiated cells increases tumor aggressiveness. We ( 134 ), and others ( 133 , 135 137 ), have observed increased tumor aggressiveness after implantation of glioma cells into previously radiated hosts. Given the potential for senescent cells to induce tissue dysfunction and inflammation, several studies have addressed the potential of metabolically active senescent cells and SASP factors to exacerbate recurrences of various cancers ( 124 , 138 , 139 ).…”
Section: Effects Of Radiation Therapy On the Gbm Microenvironmentmentioning
confidence: 81%
“…Duan et al showed that irradiation of normal brain before tumor cell implantation contributed to aggressive tumor growth, which suggested a brain tumor microenvironment-induced, tumor-extrinsic effect (66). Tumor microenvironment (TM) is mainly composed of epithelial cells, stromal cells, extracellular matrix (ECM) components or immune cells (67).…”
Section: Inhibiting Stat3 Decreased Radiation-induced Aggressive Behamentioning
confidence: 99%